EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN SELF ESTEEM - Armila Armila (Jurnal Bimbingan Penyuluhan Islam, 2021)
From the results of the research, it can be concluded that the existence of group counseling facilities can provide effective results for efforts to increase or develop self-esteem or Self Esteem for students. The results are in the form of showing an increase in the number of samples studied. In some of the experimental groups, they have a sense of self-confidence or self-efficacy, as evidenced by looking at the test results in the two different groups. Group counseling guidance has been applied so that individuals in the group experience improvements and changes based on the results of the research, the discussion section and the results of the conclusions that have been studied. The following are suggestions for the continuation of this research